Risk factors of postoperative complications of gastrointestinal tumor in elderly patients - Huiqiu Liang; Yan Luo (Guoji laonian yixue zazhi)
[Objective] To investigate the risk factors of postoperative complications of gastrointestinal tumors in elderly patients. [Methods] A total of 242 elderly patients undergoing elective gastrointestinal tumor surgery from January 2016 to January 2017 were selected for retrospective analysis, and preoperative general conditions, preoperative complications, preoperative laboratory tests and other examination indicators, surgical and anesthesia-related factors were collected.Univariate and multivariate logistic regression analysis were used to statistically analyze the influencing factors of postoperative complications. [Results] A total of 71 (29.34%) patients developed postoperative complications during hospitalization.Univariate analysis showed that there were significant differences in American Society of Anesthesiologists classification, New York Heart Association classification, Barthel index, minimally invasive surgery, preoperative chronic renal insufficiency, preoperative abnormal lung imaging, preoperative urea nitrogen level, preoperative activated partial thromboplastin time and operation time between patients with complications and those without complications (P<0.05).Multivariate logistic regression analysis showed that Barthel index ≤60, operation time and abnormal preoperative lung imaging were independent risk factors for postoperative complications of gastrointestinal tumors in elderly patients (P<0.05), and minimally invasive surgery was a protective factor (P<0.05). [Conclusion] Elderly patients with gastrointestinal tumors with Barthel index ≤60, length of operation, and abnormal preoperative lung images have a higher risk of postoperative complications and should be concerned.